Pengaruh Stres Kerja Dan Transformasi Digital Terhadap Kinerja Karyawan Dengan Work Engagement Sebagai Variabel Intervening: Studi Pada Karyawan Toko Buku Gramedia Di Kota Semarang - Cinta Dina Puan Maharani (Diponegoro Journal of Management, 2026)
This study aims to analyze the effect of job stress and digital transformation on employee performance at Gramedia Bookstore in Semarang City and to examine the role of work engagement as an intervening variable in this relationship. The study seeks to provide a comprehensive understanding of how job stress influences employee performance, both directly and indirectly through employees’ level of work engagement. This study uses a quantitative method using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, with data analysis conducted using SmartPLS 4.0. Data were collected through non-probability sampling using a total sampling technique by directly distributing questionnaires to employees of Gramedia Bookstore in Semarang City. A total of 50 respondents who met the research criteria were included in the study. The results of the study indicate that job stress has a negative and significant effect on employee performance, while digital transformation has a positive and significant effect on employee performance. In addition, job stress has a positive but insignificant effect on work engagement, whereas digital transformation has a positive and significant effect on work engagement. Work engagement also has a positive but insignificant effect on employee performance. Furthermore, work engagement is unable to mediate the effect of job stress on employee performance as well as the effect of digital transformation on employee performance. Therefore, it can be concluded that the influence of job stress and digital transformation on employee performance is more dominant through direct effects rather than through work engagement as a mediating variable.